2015
DOI: 10.3390/w7116651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen and Irrigation Application on Water Movement and Nitrogen Transport for a Wheat Crop under Drip Irrigation in the North China Plain

Abstract: For improving water scarcity and groundwater pollution from agriculture, two-year experiments (2011)(2012)(2013) with three water levels (0.3, 0.5 and 0.8 evaporation (E) in 20-cm-diameter pans) and four nitrogen (N) levels (120, 140 and 190 kg·ha in 2013) were conducted to study effects of water and N availability on water movement and N transport for a wheat crop under drip irrigation in the North China Plain. The results indicated that under drip irrigation, deep percolation at 1-m depth was stable at 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…They also found that drip irrigation reached the highest yield under moderate water and N level, whereas furrow irrigation had the largest yield under high water and N level in an eggplant study. Sui et al (2015) reported that lower water application accompanied by higher N level (190 and 290 kg ha −1 ) largely reduced the deep percolation, whereas the interaction of irrigation and N level had no significant impact on NO 3 − leaching over 0-100 cm in a wheat study.…”
Section: Core Ideasmentioning
confidence: 95%
See 1 more Smart Citation
“…They also found that drip irrigation reached the highest yield under moderate water and N level, whereas furrow irrigation had the largest yield under high water and N level in an eggplant study. Sui et al (2015) reported that lower water application accompanied by higher N level (190 and 290 kg ha −1 ) largely reduced the deep percolation, whereas the interaction of irrigation and N level had no significant impact on NO 3 − leaching over 0-100 cm in a wheat study.…”
Section: Core Ideasmentioning
confidence: 95%
“…As the only source of water input in solar greenhouses, irrigation plays a critical role in controlling water and N dynamics in the soil, and both irrigation method and level could result in a great difference in water use efficiency (WUE), N use efficiency (NUE), and nitrate leaching. Compared with furrow irrigation, drip irrigation often leads to less water and N leaching (Behera & Panda, 2009;Chilundo, Joel, Wesström, Brito, & Messing, 2018;Sui, Wang, Gong, Xu, & Zhang, 2015;Wei, Ma, Wang, & Wang, 2012), higher crop yield (Badr, Abou-Hussein, El-tohamy, & Gruda, 2010;Tw, 1980), and greater WUE and NUE (Du, Cao, Liu, Gu, & Cao, 2017;Hassanli, Ebrahimizadeh, & Beecham, 2009;Zotarelli et al, 2008), largely due to its lower application rate and higher application frequency, which help maintain favorable soil water conditions for crop growth. On the other hand, reducing irrigation to a certain level has been proved to be a great strategy to improve water productivity and NUE in crops and vegetables, such as maize (Zea mays L.), eggplant (Solanum melongena L.), and tomato (Solanum lycopersicum L.) (Aujla, Thind, & Buttar, 2007;Chen et al, 2013;Favati et al, 2009;Gheysari, Miriatifi, Bannayan, Homaee, & Hoogenboom, 2009;Mansouri-Far, Sanavy, & Saberali, 2010;Patane, Tringali, & Sortino, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional applied dosage is 290 kg N hm -2 per season in this area, which is much higher than crop requirement. Some researches demonstrated that N application rates in wheat fields may be significantly reduced compared to common farmers' practice, without negatively affecting grain yield, and the fertilizer leaching and residual will be much less (Hartmann et al, 2015;Sui et al, 2015). Determination of the optimal N fertilization is as much important as water management because yield may not increase linearly with N fertilizer (Shi et al, 2013;.…”
Section: Introductionmentioning
confidence: 99%
“…With economic and social development, water contamination has become a serious problem in many countries [1][2][3]. With control of point source contamination, nonpoint source (NPS) contamination has become dominant cause of water contamination due to its multi-source, wide distribution, the difficulty of controlling it and so on [4][5][6].…”
Section: Introductionmentioning
confidence: 99%